Was There an Altar or a Temple in the Sacred Precinct on Mt. Gerizim? - Pummer, Reinhard (Journal for the study of Judaism, 2016)
After the recent excavations by Itzhak Magen on the main summit of Mount Gerizim it has become clear that the Samari(t)an sanctuary stood within a sacred precinct in the Persian and Hellenistic times. So far, no direct evidence of the nature of the sanctuary has been unearthed. The excavator and many contemporary scholars assume it was a temple building. However, some scholars question the accuracy of this assumption and believe that the sanctuary more likely was an altar. This paper reviews both the arguments that speak for an altar and those that speak for a walled and roofed temple.